Electrochemical techniques for dating metallic heritage - Doménech-Carbó, Antonio (Anejos a Cuadernos de Prehistoria y Arqueología, 2023)
In the last years a series of electrochemical methods aimed to date metal artifacts have been devised. These are based on the voltammetry of immobilized particles methodology, a solid state electrochemical technique that permits the use of samples from the metal patina of few nanograms. The state of the art is revised summarizing the dating methods proposed for lead, copper/bronze, leaded bronze and gold.